Dendrapta nasicola n. sp. (Copepoda: Siphonostomatoida: Lernaeopodidae) a parasite from the olfactory sacs of Bathyraja scaphiops (Norman, 1937) in the South Western Atlantic - IRIGOITIA,MANUEL M. (2020)
Abstract During a parasitological survey of the olfactory sacs of 21 species of Rajiformes (Chondrichthyes) from the Southwestern Atlantic Ocean, copepods referable to DendraptaKabata (1964) (Siphonostomatoida: Lernaeopodidae) were found parasitizing the cuphead skate Bathyraja scaphiops (Rajiformes: Arhynchobatidae). Morphological analyses using both light and electron microscopy revealed that they belong to a new species. It can be easily distinguished from its congeners by the ratio between lengths of posterior process and trunk (1:0.8), the large to width ratio of trunk (1:0.7) and the armature of the antennule (1, 1, 5 + 1 aesthete). Dendrapta cameroni longiclavata is raised to full specific status, as Dendrapta longiclavata n. comb. Kabata & Gusev, 1966.